2021
DOI: 10.1186/s13717-021-00330-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of window size on remote sensing-based prediction of forest structural variables

Abstract: Background Determining the appropriate window size is a critical step in the estimation process of stand structural variables based on remote sensing data. Because the value of the reference laser and image metrics that affect the quality of the prediction model depends on window size. However, suitable window sizes are usually determined by trial and error. There are a limited number of published studies evaluating appropriate window sizes for different remote sensing data. This research inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…Tis is in agreement with Kayitakire et al [15], who found that a small window size better predicted tree height in a low-diversity spruce forest. In contrast, Ozkan and Demirel [30] detected an inverse pattern between these two variables in monospecifc temperate forest stands. Ultimately, information collected at one scale for a given ecosystem may be totally inappropriate for addressing questions at another scale or a diferent ecosystem [75,76], thus reinforcing the need for multiscalar sampling designs capable of capturing forest community variation on its diferent attributes [77].…”
Section: Te Efect Of Changing Scalementioning
confidence: 77%
See 4 more Smart Citations
“…Tis is in agreement with Kayitakire et al [15], who found that a small window size better predicted tree height in a low-diversity spruce forest. In contrast, Ozkan and Demirel [30] detected an inverse pattern between these two variables in monospecifc temperate forest stands. Ultimately, information collected at one scale for a given ecosystem may be totally inappropriate for addressing questions at another scale or a diferent ecosystem [75,76], thus reinforcing the need for multiscalar sampling designs capable of capturing forest community variation on its diferent attributes [77].…”
Section: Te Efect Of Changing Scalementioning
confidence: 77%
“…Tis is relevant because it entails that, when setting a study that aims at predicting diferent forest attributes from remote sensing, it is necessary to identify the proper scale both for feld measurements and texture window that best predicts these attributes [72,73]. However, there is no consensus on the plot-window size for each variable, since this variation seems to respond to diferences in the type of forest being studied, the resolution of the images used, and the forest attributes being quantifed [29,30,74]. For instance, our results showed that mean tree height prediction peaks at small plot-window sizes, whereas basal area is best predicted at large plot-window sizes.…”
Section: Te Efect Of Changing Scalementioning
confidence: 99%
See 3 more Smart Citations